Community nurse’s role in the COVID-19 crisis situation: a case study of COVID-19 patients under home isolation - Issarasongkhram , Mila (Journal of Medical and Public Health Region 4, 2023)
This qualitative study aimed to create guidelines for nursing home isolation for COVID-19 patients according to the role of community nurse in the crisis COVID-19 situation or dangerous communicable disease that require similar nursing care. Key Informants were selected as the specific which divided into 2 groups consisting of 1.COVID-19 case study step down after admitted at the hospital for at least 10 days then discharged for continuous treatment at home known as home isolation and 2.the four registered nurses who followed up COVID-19 patients under home isolation.The tool of the study was a changes in patient records, the interview questionnaires is health deviation self-care requisites and nursing record forms for content analysis. The results showed that a case study of Thai female at age 79 years has underlying disease chronic obstructive pulmonary disease, rheumatoid arthritis, asthma, hyperlipidemia and hypertension. The chest X- ray found the lower lung lobes on both sides are thickly. After receiving antiviral drugs, those symptoms were improved without complications and discharged for home isolation after that. The problems of health deviation self-care requisites are psychological problems, stress, complications of disease, prevention and control of infectious disease transmission. Therefore, the role of community nurses should be design for care that corresponds to the specific problem. The nurse should assess the patient’s health condition and design counseling case by case so that patients can take care of themselves and reduce anxiety. The advice starting from notification treatment isolation and empowerment for the patients to practice continually should be given. Recommendations should be clearly communicated between community health care teams. There is continuous care plan for each patient according to their problems condition in order to take care of COVID-19 step down who are admitted until discharge and rehabilitation at home. As a result, the patients can take care of themselves and reduce infection in the community.